The method of assessing the hidden economy and its application to the financial system - Raximjonov Jaxongir Nabievich (Genius Journals, 2025)
This article describes large-scale reforms aimed at creating favorable conditions for doing business in the tax and financial sectors, improving the investment climate and further strengthening the confidence of business circles in our republic in recent еars. At the same time, such areas as underground trade and public catering, road transport, housing construction and repair, the provision of personal services were studied, scientific and practical conclusions and proposals were formed on foreign experience and its application in our country
Keywords: tax revenues; analysis; risks